91 To What Extent are Patients' Future Care Preferences Shared Between Secondary and Primary Care? A Retrospective Chart Review. (6th February 2020) - Hopkins, S A; Athauda, P; Halliday, A; Honney, K; Jakupaj, A; Kaneshamoorthy, M; Mark, H; Pampali, C; Van der Poel, L; Ondhia, D; Balogun, A; Vincent, M; et al.
Abstract: Introduction: When a doctor is informed of a patient's future care preferences if they were to lose capacity, there is an ethical and legal obligation to share this information with the treating medical team. In frail older patients, conversations about treatment preferences often occur during hospital admission. We sought to assess the communication of these preferences to the patient's GP. Methods: Retrospective chart review of consecutive discharges from acute geriatric wards across seven hospitals. Records were excluded if the patient was admitted for less than 48 hours, was under orthogeriatric care, or died in hospital. Results: 339 notes were included, 41-50 from each hospital. GPs were informed of the resuscitation status of 28% of all patients. 52% of patients had an inpatient DNACPR, the GP was informed of 54% of these. 36% of patients had an inpatient ceiling of treatment documented, of which GPs were informed of 19%. 53% of hospital DNACPRs were converted into community DNACPRs on discharge: GPs were informed of only 24% of new community DNACRPs. 47% of patients discharged with a new community DNACPR lacked capacity to be involved in that decision; for just 6% of these was the GP asked to review the DNACPR order in the community. Inpatient Advance Care Planning (ACP) discussions were held for 9% of patients, of which the GP was informed in 59% of cases. 49% of ACP conversations involved the next-of-kin but not the patient. Among patients who had a new DNACPR decision made during their admission (n=124), there was documentary evidence in only 25% that the patient or next-of-kin was informed whether this was time-limited or indefinite. Conclusions: Communication from hospitals to GPs about resuscitation, ceiling of care and ACP discussions is very limited. For patients who have expressed ongoing future care preferences, there is a legal obligation to share this information with the treating medical team, which on discharge is the GP. There is poor documentary evidence of discussions with patients about whether DNACPR decisions are time-limited or indefinite. Furthermore, many hospitalised frail patients lack capacity to make DNACPR decisions but they may subsequently regain capacity, particularly those with delirium. Despite this, GPs are rarely asked to review new community DNACPRs, including those made for patients without capacity.